Smear-positivity of Tuberculosis in in-door patients of DHQ hospital, Swabi, Pakistan - Ali, Farooq; Ahmed, Shehzad (International Journal of Pathology, 2020)
Background: Tuberculosis is an infectious disease with a historical background caused by acid fast bacillus bacterium, Mycobacterium tuberculosis which is transferred by droplets. It contributes to affect about one-third population globally. Tuberculosis has a wide prevalence and death rate just second to the HIV infection.Materials and methods: The study was conducted during a year from January-December 2018 to observe the infected rate of tuberculosis in district Swabi. The aim of the study is to pinpoint the prevalence rate of the infection to speed up the access of health care programs to the infected people for effective treatment in the population. The suspected patients were belonging to district Swabi. The sputum was sampled, covered and labelled carefully from all the suspected patients. Each sample was smeared, stained on slid and was examined carefully for acid fast bacilli.Results: The overall result examined was 18.15% in which male contributed 53.81% and female 46.18%. The highest prevalence rate, 26.27%, was observed in the age group 16-30. The highest frequency rate in male was observed in the age group 61-75 while in female in the age group 16-30. Moreover, the farmer occupation was more infective in comparison to others.Conclusion: Results concluded that, the prevalence rate of tuberculosis is quite high in the study area which is due to the lake of health education, awareness and medical care